2016
DOI: 10.1080/17453674.2016.1210533
|View full text |Cite
|
Sign up to set email alerts
|

Increased mortality after lower extremity fractures in patients <65 years of age

Abstract: Background and purpose — The association between mortality and lower extremity fractures (other than hip fractures in older individuals) is unclear. We therefore investigated mortality in adults of all ages after lower extremity fractures that required inpatient care.Patients and methods — Diagnosis code (ICD10), procedure code (NOMESCO), and 7 additional characteristics of patients admitted to the trauma ward at Central Finland Hospital were collected between 2002 and 2008 (n = 3,567). Patients were followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 18 publications
1
11
1
3
Order By: Relevance
“…For hip fractures Standardized Mortality Rate is 2.0 for women and 3.0 for men. 5 In India, Hip fracture crude incidence above the age of 50 years was 129 per 100,000. 6 There are various studies pertaining to the early mortality of proximal femur fractures all over the world and none from subcontinent.…”
mentioning
confidence: 99%
“…For hip fractures Standardized Mortality Rate is 2.0 for women and 3.0 for men. 5 In India, Hip fracture crude incidence above the age of 50 years was 129 per 100,000. 6 There are various studies pertaining to the early mortality of proximal femur fractures all over the world and none from subcontinent.…”
mentioning
confidence: 99%
“…While the mortality rate of older patients with a pelvic ring fracture have been reported by several authors, detailed assessment of the burden and impact of these injuries requires comparison with the mortality rates of other patient cohorts [713, 18]. Hill et al reported excess mortality compared to the reference population in patients with a pubic rami fracture, i.e., mortality risk remained elevated after the pubic fracture throughout the 60-month study period [8].…”
Section: Discussionmentioning
confidence: 99%
“…In CFH, one OR is dedicated for orthopedic IEO every day during office hours and one OR for all emergency operations outside office hours. One OR is reserved for GLOs 4 days a week (Tuesday to Friday) during normal Finnish office hours (7.30–15 o’clock).…”
Section: Methodsmentioning
confidence: 99%